Effectiveness of information services using cooperative learning approach with Jigsaw Technique to improve understanding of bullying - Fatmawati Sitepu; Yeni Karneli (Universitas Negeri Padang, 2022)
Bullyingis a deviant behavior that many students do, bullyingby students do can occur because of students' misunderstandings about the nature of this deviant behavior. One way to increase students' understanding of bullying is to provide information services using a cooperative learning approach with a jigsaw technique. The aims of this research aretested the significant difference in understanding bullying between the experimental group students who participated in the information service usingcooperative learning approach with jigsaw techniquewith control group students who participated in information services using lecture and question and answer methods.The research method used is a quantitative research method. The total sample of this study was 32 students with 16 students in the experimental group and 16 students in the control group. The results showed that there was a significant difference in understanding of bullying between experimental group students who are given information services using a cooperative learning approach with jigsaw techniques and control group students who are given information services using lecture and question and answer methods. Thus, the information service uses a cooperative learning approach with an effective jigsaw technique to increase students' understanding of bullying.